PLGA-Chitosan nanoparticle-mediated gene delivery for oral cancer treatment: A brief review - Bakar, Latifah Munirah; Abdullah, Mohamad Zakkirun; Doolaanea, Abd Almonem; Ichwan, Solachuddin J. A. (IOP Publishing Ltd, 2017)
Cancer becomes a serious issue on society with increasing of their growth and proliferation, either in well economic developed countries or not. Recent years, oral cancer is one of the most threatening diseases impairing the quality of life of the patient. Scientists have emphasised on application of gene therapy for oral cancer by using nanoparticle as transportation vectors as a new alternative platform in order to overcome the limitations of conventional approaches. In modern medicine, nanotechnologies’ application, such as nanoparticles-mediated gene delivery, is one of promising tool for therapeutic devices. The objective of this article is to present a brief review summarizes on the current progress of nanotechnology-based gene delivery treatment system targeted for oral cancer.